2002
DOI: 10.1200/jco.2002.06.102
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma in Children: Results of the First Prospective Study of the International Society of Pediatric Oncology Group

Abstract: Survival for pediatric HCC patients is significantly inferior to that for children with hepatoblastoma. Complete tumor excision remains the only realistic chance of cure, although it is often prevented by advanced disease. The presence of metastases is the most potent predictor of poor prognosis. A prospective worldwide cooperation in the field of pediatric HCC should be encouraged to look for novel therapeutic concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
233
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(258 citation statements)
references
References 30 publications
16
233
0
7
Order By: Relevance
“…2017; 17(8):e11837. Many of the previous studies have reported chronic hepatitis B related cirrhosis as the most common underlying cause of pediatric HCC (14), however, we didn't have any case of HBV related cirrhosis in these 30 cases of pediatric HCC. We believe it is due to extensive and successful vaccination in Iran and significant decrease in the number of HBVs in the current generation of pediatric age group.…”
mentioning
confidence: 64%
“…2017; 17(8):e11837. Many of the previous studies have reported chronic hepatitis B related cirrhosis as the most common underlying cause of pediatric HCC (14), however, we didn't have any case of HBV related cirrhosis in these 30 cases of pediatric HCC. We believe it is due to extensive and successful vaccination in Iran and significant decrease in the number of HBVs in the current generation of pediatric age group.…”
mentioning
confidence: 64%
“…HCC is the second most common hepatic malignancy in children and accounts for less than 0.5% of all pediatric cancer [34]. An estimated 0.5-1.0 cases per million children is the reported relative frequency for HCC [35].…”
Section: Hepatoblastoma and Hepatocellular Carcinomamentioning
confidence: 99%
“…Other combination regimens include cisplatin plus doxorubicin with response rates 18 to 49 percent (Lee et al, 2004;Czauderna et al, 2002), cisplatin, mitoxantrone, and continuous infusion 5-FU with objective response rates 24 to 27 percent in two different studies (Yang et al, 2004;Ikeda et al, 2005), cisplatin, epirubicin and infusional 5-FU with a response rate 15 percent (Boucher et al, 2002;) cisplatin, doxorubicin plus capecitabine with a response rate of 24 percent (Park et al, 2006).…”
Section: Gemcitabine and Cisplatinmentioning
confidence: 99%